Prevalence and Associated Risk Factors of Suicidal Ideation Among Brazilian Pregnant Women: A Population-Based Study - Faisal-Cury, Alexandre; Oliveira Rodrigues, Daniel Maurício; Matijasevich, Alicia; Tarpinian, Fernanda; Tabb, Karen (Frontiers in Psychiatry, 2022)
Background: Suicide is a leading cause of death during the perinatal period in high-income countries (HIC). There remains a lack of population-based studies about suicidal ideation (SI) during pregnancy across low and middle income countries (LMIC). Objective(s): Using the case of Brazil, we aim to estimate the prevalence of SI during pregnancy and its association with antenatal depression (AD) and sociodemographic factors in a LMIC. Method: We used data from the Brazilian National Survey (PNS-2019), a population-based study, with a complex and probabilistic sampling method. Of the 27,136 women of reproductive age (15 to 49 years old) who participated in the PNS, a total of 769 women reported being pregnant at the time of the interview. All PNS participants answered the Patient Health Questionnaire-9 (PHQ-9) and a questionnaire with sociodemographic data. SI was defined as any answer to the PHQ-9 item 9 other than 0 (not at all). Logistic regression models were performed to obtain crude and adjusted odds ratios (aOR) and 95% confidence intervals (95% CI) for the association between explanatory variables and SI during pregnancy. Results: Among 769 women, 33 (3.9%, 95% CI: 3.0%-5.1%) reported SI during pregnancy. In the adjusted analysis, higher odds of SI were associated with being 20 to 34 years old (aOR:0.24, 95% CI: 0.08-0.74) or 35 to 49 years old (aOR:0.15; 95% CI: 0.04-0.50), having 9 to 11 years of education (aOR 0.23, 95% CI: 0.61-0.86), acheiving the highest family income category (aOR:0.08, 95% CI: 0.01-0.58), not living in the South/Southeast regions of Brazil (aOR:5.52, 95% CI: 2.36-12.9), and having probable mild AD (aOR:10.5 95% CI: 2.3-47.9) or moderate AD (aOR:241.3, 95% CI: 58.4-996.7). Conclusion(s): In Brazil, SI affects almost 4% of pregnant women and is associated with sociodemographic vulnerability. Clinically, women with mild symptoms of depression may also experience SI during pregnancy. These findings are important for designing effective perinatal mental health interventions in LMICs.